Petra Heidrich's research work in the context of the development of South Asian Studies at the ZMO (1992-2000) - Hafner, Annemarie (2010)
Abstract: "The aim of this paper is to remember Petra Heidrich, a friend and colleague of Annemarie Hafner, who died much too soon. Special attention is given to Petra Heidrich’s scientific work, which can be subsumed under the theme of »Agrarian and Peasant Studies and Transformation of Traditional Social Structures and Reform Movements in the 19th and 20th Centuries in India«. At the same time, the paper seeks to honour the contribution Petra Heidrich made to the prosperity of the ZMO during its founding stages and initial positioning. Starting from these memories, Annemarie Hafner tries to develop conceptual suggestions on how, from today’s viewpoint, the research field of agrarian and peasant studies can be revived, as they currently lie fallow in the landscape of German social historical research, and in particular, within South Asian Studies." (author´s abstract)